Paired Associative Stimulation Delivered by Pairing Movement‐Related Cortical Potentials With Peripheral Electrical Stimulation: An Investigation of the Duration of Neuromodulatory Effects. Issue 4 (5th June 2017) - Olsen, Sharon; Signal, Nada; Niazi, Imran Khan; Christensen, Thomas; Jochumsen, Mads; Taylor, Denise
Abstract : Background: Novel paired associative stimulation (novel‐PAS), delivered by pairing movement‐related cortical potentials (MRCPs) with electrical stimulation of somatosensory afferents, is an innovative neuromodulatory intervention. Novel‐PAS results in increased corticomotor excitability and has potential as a rehabilitative adjunct to improve outcomes following stroke. The duration of its excitatory effect has important implications for how this novel PAS intervention might be applied within a traditional therapy session, but previous research has not explored its effects beyond 30 min post‐intervention. Objective: The objective was to explore changes in corticomotor excitability in healthy participants, over a 60‐min period following a single session of novel‐PAS. Materials and Method: Ten healthy adults completed a single session of novel‐PAS, delivered by pairing 50 MRCPs with peripheral electrical stimulation. TMS was used to elicit motor evoked potentials (MEPs) of the tibialis anterior (TA) muscle, immediately prior to the intervention, and at 0, 30, 45, and 60 min post‐intervention. Results: When compared with pre‐intervention, there was a statistically significant increase in the mean TA MEP amplitudes at 0 ( p  = 0.006), 30 ( p  = 0.006), 45 ( p  = 0.027), and 60 min post‐intervention ( p  = 0.020). Conclusion: Corticomotor excitability is increased for 60 min following this novel‐PAS intervention. Future research could investigate the optimal method of combining this neuromodulatory technique with traditional therapy.